Cellular coupling determines scale-invariant behavior of neurons in suprachiasmatic nucleus. (1st December 2020) - Zhou, J.; Gu, X.; Gu, C.; Yang, H.; Weng, T.; Rohling, J.H.T.
ABSTRACT: The main clock in mammals, located in the suprachiasmatic nucleus (SCN) of hypothalamus, not only regulates the daily rhythms in physiological and behavioral activities, but also plays a key role as one of the control nodes in the brain regulating behavioral activity. As such, it induces scale-invariance in the temporal patterns of behavioral activity and of multi-unit neural activity of the SCN network. In particular, the scale-invariant patterns maintain across multiple time scales from 3 minutes to 10 hours, characterized by a scaling exponent around 1. Thus far, no study found the origin of the scale-invariance of the SCN network. Using the method of correlation-dependent balance estimation of diffusion entropy (cBEDE), we found that scale-invariance also exists in the individual neurons of the SCN, and the scale invariance properties are significantly increased when the neurons are coupled in a network of neurons. Improved scale invariance in the single neurons is, therefore, imposed by the emergent network properties of the SCN network. Our findings show that the scale-invariance of the SCN can already be found at the level of the individual neurons and that the application of a scale invariance measure, such as cBEDE, can help in determining the network status of the SCN.